Unintentional Weight Loss in Older Adults: A Geriatric Interprofessional Simulation Case Series for Health Care Providers - Rebekah Mulligan; Melissa Gilmer-Scott; Dana Kouchel; Davia Nickelson; Atousa Safavi; Margaret Drickamer; Ellen Roberts (Association of American Medical Colleges, 2017)
Introduction Interprofessional teams can provide better care and management of complex geriatric patients. Unintentional weight loss in older patients can lead to significant morbidity and mortality and functional decline. This simulation curriculum focuses on teaching learners from all health care professions how to use the Carolina Geriatrics Workforce Enhancement Program unintentional weight loss tool and flowchart (T&F) to identify, diagnose, and create a plan of care for weight loss in geriatric patients. Methods A presentation on use of the T&F and two standardized patient cases utilizing the T&F in an interprofessional team are included. Case 1 presents a 71-year-old male with dementia who has lost 20 pounds, with weight loss secondary to cognitive impairment, denture problems, oral candidiasis, and polypharmacy. Case 2 presents a 67-year-old female with a history of depression and breast cancer who has lost 15 pounds, likely related to alcohol dependence, social isolation, oral cancer, and food insecurity. Pre- and posttests measure knowledge gained through the course. Results Overall knowledge of unintentional weight loss improved in the 14 learners who participated in two pilot sessions. Test scores improved an average of 1.2 points from pre- to posttest. Participants felt that interprofessional teams increased the quality of care provided to patients and job satisfaction. Discussion This tool can be utilized by practitioners from multiple disciplines. By completing the curriculum, learners gain knowledge of how to identify geriatric patients with significant weight loss, determine next steps in diagnosis and workup, and work in an interprofessional group.